SURAT PERINTAH PENGHENTIAN PENYIDIKAN (SP3) DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI - Sugama, I Dewa Gede Dana (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 3 No 1 (2014), 2014)
This study discusses about Inadequacy Corruption Eradication Commission In Issuing Warrant Termination of Investigation In Corruption Case. The Commission is authorized to issue a warrant termination of the investigation and to determine the actions taken when the Commission which investigated corruption Commission was not enough evidence . The conclusion of this study is, first Corruption Eradication Commission is authorized to issue an Order for Termination of Investigation in accordance with Article 40 of Law No. 30 Year 2002 about Corruption Eradication Commission, consideration of the logic of juridical is that the Commission is not a core law enforcement within the criminal justice system and just as independent institutions that can be dismissed if there is no corruption in our country. The arrangement of Article 40 of Law No. 30 of 2002 is prudential or attitude of prudence principle for the Commission to work accurately , efficiently and professionally
Keywords: Corruption Eradication Commission; Termination Warrant Investigation; Corruption